Yes‐Associated Protein is up‐regulated by mechanical overload and is sufficient to induce skeletal muscle hypertrophy. Issue 13 (8th May 2015) - Goodman, Craig A.; Dietz, Jason M.; Jacobs, Brittany L.; McNally, Rachel M.; You, Jae-Sung; Hornberger, Troy A.
Abstract : Mechanically‐induced skeletal muscle growth is regulated by mammalian/mechanistic target of rapamycin complex 1 (mTORC1). Yes‐Associated Protein (YAP) is a mechanically‐sensitive, and growth‐related, transcriptional co‐activator that can regulate mTORC1. Here we show that, in skeletal muscle, mechanical overload promotes an increase in YAP expression; however, the time course of YAP expression is markedly different from that of mTORC1 activation. We also show that the overexpression of YAP induces hypertrophy via an mTORC1‐independent mechanism. Finally, we provide preliminary evidence of possible mediators of YAP‐induced hypertrophy (e.g. increased MyoD and c‐Myc expression, and decreased Smad2/3 activity and muscle ring finger 1 (MuRF1) expression). Abstract : We examined YAP protein expression and mTORC1 activation in overloaded muscles. We also examined the effect of transient YAP overexpression on muscle fiber size. Overload‐induced increases in YAP and mTORC1 signaling follow different time courses. YAP overexpression induced mTORC1‐independent muscle fiber hypertrophy. YAP is a novel mTORC1‐independent regulator of skeletal muscle mass.